Metatalk and metalinguistic knowledge: the interplay of procedural and declarative knowledge in the classroom discourse of first-language grammar teaching. Issue 3 (5th October 2021) - Watson, Annabel M.; Newman, Ruth M. C.; Morgan, Sharon D.
Abstract: 'High-quality talk' is a fundamental principle of many approaches to teaching grammar. However, relatively few studies have attempted to characterize this talk with attention to the ways in which classroom dialogue might engender metalinguistic thinking. This paper explores how the concepts of procedural and declarative metalinguistic knowledge may be applied to classroom discourse in order to identify the problems and potentials of grammatical 'Metatalk'. The data is drawn from observations of functionally-oriented grammar lessons in 17 classrooms across England. This opportunity sample was drawn from the intervention group of a randomized control trial, all of whom were working within a pedagogical model which embeds attention to grammar as a resource for meaning-making within the teaching of writing. Given the impact of effective teacher-student dialogue on student learning, studies such as this are valuable for illuminating how classroom talk operates within the teaching of grammar for writing. The findings particularly reveal the role of teacher-guided talk during collaborative writing activities in facilitating bi-directional transfer between declarative and procedural metalinguistic knowledge.